Comparative Analysis of Embankment Slope Stability using Geofoam - Sudjatmiko, Eddy Triyanto; Hairunnisa, Arsila (President University, 2025)
Landslides caused by land movement due to unstable soil are one of the causes of infrastructure damage such as cracks or collapse and can pose various threats to humans. The development of technology in geotechnics called geofoam material which is also known as lightweight material can be solution. This study aims to determine whether geofoam can be used as a partial replacement material for soil by comparing the results that have been analyzed using Plaxis 2D software. Landslides with existing silt clay soil conditions occur because the safety factor = 1 in undrained conditions. Meanwhile, on embankment soil built with geofoam measuring 1 x 4 m on a 15 m thick embankment and a slope of 1:2, it shows that the safety factor on the slope increases to 1.5 for undrained conditions and 1.9 for drained conditions. A reduction in the amount of geofoam by 37% was carried out and the SF figures were 1.34 for undrained and 1.6 for drained. These results have met the requirements of SNI 8460:2017, where SF>1.25 and external load of 25 kN/m2Â did not change the safety factor on the geofoam embankment. In addition, the displacement in undrained and drained conditions on the existing soil reached 27 cm and 31 cm respectively, much different from the displacement on the geofoam which was only 2.3 cm and 2.7 cm. The results of the effective stress distribution pattern and shear strain showed that the activity that occurred on the embankment with geofoam was very low compared to the existing soil. It can be concluded that geofoam material can replace part of the embankment, because it has been proven to be able to stabilize the slope on the embankment. In addition, the more geofoam used, the higher the stability of the embankment.